The Effect of a Balance Snack, Porridge (Haleem) on Malignancy Treatment-Related Weight Loss in Children - Shahrooz Bent Yaghoob; Mousa Salehi; Soheila Zareifar; Seyed Mohamadreza Hoseini Poya; Abbas Yousefinejad (Shiraz University of Medical Sciences, 2015)
Background: Adequate and appropriate food and nutrition during treatment of cancer plays an outstanding role in response to treatment, patient quality of life and the reduction of treatment cost. In this period, children are exposed to malnutrition because, they firstly need more substrate for treatment of this illness and second, they have fewer amounts of macro and micro nutrients storages. Several studies have shown that supplementation has anti cachectic effects in cancer patients. Objectives: This study evaluated the clinical effects of a protein and energy dense nutritional supplement in a group of pediatric cancer patients receiving active chemotherapy treatment. Materials and Methods: The study was a randomized controlled clinical trial. Seventy patients diagnosed with pediatric malignant disease and receiving intensive chemotherapy were included. Thirty-five patients received a nutritional supplement (Haleem) in addition to their regular food intake and thirty-five patients did not receive any supplementation. Patients are examined and their data (weight, height, albumin, pre albumin, globulin, total protein) recorded at baseline and after 45 days. Results: At 45 days weight loss was significant in the control group (P < 0.001). On the other hand we had weight gain in the treatment group (P < 0.001). In addition, remission rate was significantly (P = 0.036) higher in the treatment group as compared to controls. Conclusions: In comparison to the result of the case and control groups, which does not receive any supplement, we found out that not only taking this kind of supplement prevented weight loss during the treatment, but also it caused weight increase in this group.